Maternal nutritional status, decision-making autonomy and the nutritional status of adolescent girls: a cross-sectional analysis in the Mion District of Ghana. (2nd November 2022) - Agaba, Monicah; Azupogo, Fusta; Brouwer, Inge D.
Abstract: A mother's nutritional status and participation in household decision-making, a proxy for empowerment, are known determinants of improved nutrition and health outcomes for infants and young children; however, little is known about the association among adolescents. We examined the association between maternal nutritional status, decision-making autonomy and adolescent girls' nutritional status. We analysed data of 711 mother–adolescent girl pairs aged 10–17 years from the Mion District, Ghana. Maternal nutritional status and decision-making autonomy were the independent variables while the outcomes were adolescent girls' nutritional status as defined by anaemia, stunting and body mass index-for-age Z -score categories. Girl-level (age, menarche status and the frequency of animal-source food consumption), mother-level (age, education level, and monthly earnings) and household-level (wealth index, food security status and family size) covariates were adjusted for in the analysis. All associations were examined with hierarchical survey logistic regression. There was no association between maternal height and adolescent girls being anaemic, underweight or overweight/obese. Increasing maternal height reduced the odds of being stunted [adjusted odds ratio (OR) 0⋅92, 95 % CI (0⋅89, 0⋅95)] for the adolescent girl. Maternal overweight/obesity was positively associated with the girl being anaemic [OR 1⋅35, 95 % CI (1⋅06, 1⋅72)]. The adolescent girl was more than five times likely to be thin [OR 5⋅28, 95 % CI (1⋅64–17⋅04)] when the mother was underweight. Maternal decision-making autonomy was inversely associated with stunting [OR 0⋅88, 95 % CI (0⋅79, 0⋅99)] among the girls. Our findings suggest that intergenerational linkages of a mother's nutritional status are not limited to childhood but also during adolescence.